Pengaruh Pola Asuh Orang Tua Terhadap Perilaku Cyberbullying Di SMA N 11 Tebo - Aditia Nafasati; Linda Fitria; Popi Radyuli (Insan Cendekia : Jurnal Pendidikan dan Kebudayaan, 2024)
Parenting patterns are the way parents educate, guide, discipline, and protect their children in an effort to achieve maturity in accordance with the norms that apply in society. This study aims to determine the extent of the influence of parenting patterns on cyberbullying behavior. The method used in this study is quantitative with the type of research, namely correlational. The study was conducted at SMA Negeri 11 Tebo in grades X, XI, and XII. The population of this study was 391 in the 2024/2025 academic year. The simple random sampling technique. The instrument in this study was a Likert scale questionnaire. Data analysis was carried out using an IBM Statistical 29 computer and Microsoft Excel. Based on the results of data processing, the calculated r value is 0.419 while the r table value is 0.138 because the calculated r is greater than the r table (0.418>0.138) it can be concluded that there is a significant influence between parenting patterns and cyberbullying behavior at SMAN 11 Tebo